A Macroeconomic Framework for Quantifying Growth and Poverty Reduction Strategies in Niger - Pinto Moreira, Emmanuel (World Bank, Washington, DC, 2012)
The authors apply the dynamic macroeconomic framework developed by Agénor, Bayraktar, and El Aynaoui (2004) to Niger. As in the original model, linkages between foreign aid, public investment (disaggregated into education, infrastructure, and health), and growth are explicitly captured. Although the nominal exchange rate is fixed, the relative price of domestic goods is endogenous, thereby allowing for potential Dutch disease effects associated with increases in aid. The authors assess the impact of policy shocks on poverty by using partial growth elasticities. They perform various policy experiments, including an increase in the level of foreign aid, a reallocation of public investment toward infrastructure, and neutral and non-neutral cuts in tariffs. The simulations show the dynamic tradeoffs that these policies entail with respect to growth and poverty reduction in Niger.